The Macapagal-Arroyo presidency and administration record and legacy, 2001-2004 : President Gloria Macapagal-Arroyo and her administration - Bautista, Victoriia A.; Abueva, Jose V.; Domingo-Tapales, Proserpina; Domingo, Ma. Oliva Z.; Nicolas, Eleanor E. (Quezon City, Philippines : University of the Philippines Press, 2004)
As a Vice President of the Philippines , Gloria Macapagal-Arroyo ascended to the precidency on January 20, 2001 upon the forced resignation of the president Joseph Estrada who was subsequently arrested, detained and tried for plunder and other crimes. Just over three years after her succession, on march 18, 2004, president Macapagal-Arroyo delivered the culminating lecture in the third University of the Philippines (UP) public lectures on the Philippine Presidency at the heroes hall in Malacañang.
Part I. The performance and promise of the Macapagal-Arroyo administration -- Part II. Governance and Local affairs -- Part III. National security, Defense and Foreign affairs -- Part IV. Human And Social Development -- Part V. Socio-economic Development -- Part VI. Cross-Cutting Issues.
Includes index.
Keywords: POLITICS AND GOVERMENT